CASH ENDOWMENT (WAKAF TUNAI) DEVELOPMENT IN THE ERA OF THE ASEAN ECONOMIC COMMUNITY - Medaline, Onny (LPPM IAIN Kudus, 2016)
The constitution No. 41 of 2004 has expanded the objects to be endowed, in general it’s not only the unmoving objects, but the moving object also becomes the object of endowments objects such as cash endowment (money). The management of endowment gets the understanding shift slowly, which is in the narrow sense as an entity limited endowments of worship only, but has now showed as the endowment understanding in the productive manner for the management of endowment property. So the system of cash endowment management needs the management models as the operational standard to use the funds maximally. In this era of MEA, cash endowment is expected to be one of the instruments to assist the government in the financial sector to develop the vital sectors that grow through existing Small and Medium Business (SMB) in the community. Instead, MEA is a challenge for modern development of cash endowment to be Islamic institutions be able to become a source of capital and investment for growth economy of community.